2019
DOI: 10.1093/ehjci/jez245
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular systolic dysfunction but not dilatation correlates with prognostically significant reductions in exercise capacity in repaired Tetralogy of Fallot

Abstract: Aims The optimal timing for pulmonary valve replacement in asymptomatic patients with repaired Tetralogy of Fallot (rTOF) and pulmonary regurgitation remains uncertain but is often guided by increases in right ventricular (RV) end-diastolic volume. As cardiopulmonary exercise testing (CPET) performance is a strong prognostic indicator, we assessed which cardiovascular magnetic resonance (CMR) parameters correlate with reductions in exercise capacity to potentially improve identification of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…Cardiopulmonary exercise testing (CPET) offers additional prognostic guidance for timing of intervention [ 8 ] but is not routinely performed in the asymptomatic or mildly symptomatic patient. In a retrospective analysis for rTOF patients with both CMR and CPET, RV ejection fraction (RVEF) < 40% but neither RV end-diastolic volume (EDV) nor end-systolic volume (ESV) was predictive of peak oxygen uptake (VO 2 ) below the established prognostic threshold of 27 ml/kg/min [ 9 ]. As severe RV dysfunction presents late, its diagnostic utility for incipient exercise intolerance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiopulmonary exercise testing (CPET) offers additional prognostic guidance for timing of intervention [ 8 ] but is not routinely performed in the asymptomatic or mildly symptomatic patient. In a retrospective analysis for rTOF patients with both CMR and CPET, RV ejection fraction (RVEF) < 40% but neither RV end-diastolic volume (EDV) nor end-systolic volume (ESV) was predictive of peak oxygen uptake (VO 2 ) below the established prognostic threshold of 27 ml/kg/min [ 9 ]. As severe RV dysfunction presents late, its diagnostic utility for incipient exercise intolerance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Babu-Narayan et al showed that in rToF patients undergoing PVR, preoperative oxygen uptake was indeed predictive of early postoperative mortality [16]. However, the relationship between RV dilatation and/or dysfunction and some CPET parameters is still poorly understood [17,18]. In addition, its potential usefulness as a tool for risk stratification and patient selection in asymptomatic adolescents and adults with rToF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the interaction between PR and tricuspid inflow potentially limits augmentation of RV cardiac output during exercise, leading to exercise intolerance. Previous CMR studies have not demonstrated any significant correlation between RV size and PR with exercise capacity [ 8 , 9 , 11 ], informing the use of modified parameters such as ventricular global function index [ 9 ]. Thus far, only right ventricular systolic dysfunction and branch pulmonary artery size discrepancy have correlated with decreased exercise capacity [ 7 , 11 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous CMR studies have not demonstrated any significant correlation between RV size and PR with exercise capacity [ 8 , 9 , 11 ], informing the use of modified parameters such as ventricular global function index [ 9 ]. Thus far, only right ventricular systolic dysfunction and branch pulmonary artery size discrepancy have correlated with decreased exercise capacity [ 7 , 11 , 51 ]. In our subgroup cohort, RVOT-VQ and RVOT-EQ correlated with VO 2-max and % predicted VO 2-max , suggesting that the abnormal intracardiac flow patterns from PR is still the link to exercise intolerance in rTOF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation